the behavior of heavy metals content in coal combustion products (ccps) and its leachate from indonesia coal power plants - Ali Rahmat Kurniawan (Puslitbang tekMIRA, 2014)
The development of many coal power plants in Indonesia has been creating Coal Combustion Products (CCPs) in a huge amount. The generating coal power plant will increase dramatically from 50 to 320 TWh in 2020. It is predicted that the total CCPs will be nearly 10.8 million tons in the same year. The large quantity of Indonesia CCPs will likely increase drastically and potentially will be a serious problem in the future. This research aims to measure heavy metals content in coal and CCPs, to assess their distribution in leachate and investigate the concentration level of heavy metals in leachate using TCLP method, and also to analyze the correlation between heavy metals content in coal, CCPs, and CCPs leachate using Pearson analysis.The analysis results show that the dominant element content in coal was boron. Moreover, the distribution of heavy metals tended to enrich fly ash. The concentration level of heavy metals fly ash and bottom ash leachates from all the power plants generally was much lower than the standard threshold. The significant level of concentration on fly ash and bottom ash was shown by boron. The concentration levels of heavy metals of coal ash leachates from two power plants were also much lower than the standard limit. The correlation between the heavy metals content of parent coal and CCPs pointed to no correlation between the variables. The heavy metals content of coal had no correlation with the concentration of heavy metals in CCPs leachate excluding nickel and chromium in bottom ash. Finally, it is recommended to assess other heavy metals concentration such as arsenic, mangan and selenium in CCPs leachate and further conduct a long-term study about the characteristics, leaching be- havior of heavy metal leachate and, their effects on the environment.